Contaminação por compostos organoclorados em boto-vermelho Inia geoffrensis de Blainville, 1817 (Cetartiodacyla: Iniidae) nos rios Negro e Branco, Norte do Brasi - RISTAU, Nathali Garcia (2016)
Humpback whales have a cosmopolitan distribution and undertake annual migrations between low and high latitudes where breeding and feeding takes place, respectively. In Brazil, the main breeding area encompasses the Abrolhos Bank at the Eastern Brazilian Coast and the feeding area of this population is located in South Georgia and South Sandwich Islands. Here, two recent records of humpback whales are reported for Maranhão State, Amazonian Equatorial Coast (AEC), one of which involves a newborn calf with remains of the umbilical cord. Additionally, an in-depth review of the stranding and observation records for this area is presented. Phylogenetic analysis placed the stranded animals within the two most common haplogroups reported for the Southern Hemisphere breeding grounds (CD and IJ). A possible extension of the species range or the recolonization of a historical breeding area along the Brazilian coast is discussed. Presented results provide evidence of distribution overlap between the humpback whale populations of the northern and southern Atlantic Ocean which will require the development of conservation strategies among neighboring countries and underline the need to develop management strategies that will allow sustainable management of the Amazonian Equatorial Coast.